Performance of variations of the dynamic elastance model in lung mechanics. (January 2017) - Laufer, Bernhard; Docherty, Paul D.; Knörzer, Andreas; Chiew, Yeong Shiong; Langdon, Ruby; Möller, Knut; Chase, J. Geoffrey
Abstract: Acute respiratory distress syndrome (ARDS) is associated with high mortality and it is a major clinical problem. A common therapy for ARDS patients is mechanical ventilation (MV). However, poorly applied MV can be potentially fatal and optimal MV settings are patient specific. Thus, choosing a good positive end expiratory pressure (PEEP)-level compromise is a clinical challenge. Physiological modeling of the lung is one way to support the selection of the optimal settings for mechanical ventilation. This research makes the reasonably well-supported assumption that optimal PEEP is in the region of minimal elastance of the lung-tissue. The first order model of pulmonary mechanics (FOM) was modified in two differing ways in order to determine the patient-specific pressure range that coincides with minimal elastance. The extensions to the FOM (multiplicative elastance correction and additive volume correction parameters) are compared and evaluated. The addition of the correction parameters ultimately improved the consistency of the modeled elastance across PEEP levels for most patients tested. The results for minimal elastance were in very similar ranges for both approaches. Although this consistency offers a partial validation of the robustness of the approaches, discernment of the optimal approach cannot be determined. Further validation across differing patient states and experimental inputs must be undertaken to determine which method is more representative of true patient physiology.